Structural Design and Fabrication for Low Loss Y-branched Polymer Waveguide Coupler Devices - Nakazaki, Fukino; Ishigure, Takaaki (2018 IEEE British and Irish Conference on Optics and Photonics (BICOP), 2018)
Along with the wide deployment of cloud computing services, the introduction of optical interconnect technology has supported the rapid growth of data throughput in datacenter over the last couple of years. So far, multimode fiber (MMF) links have been widely installed in datacenter networks, hence the limitation of bandwidth distance product of MMF links is a current issue. In the future, wavelength division multiplexing (WDM) transmission technology could be applied even to the MMF links, by which the transmission capacity could increase because multiple optical signals with different wavelengths are multiplexed in one fiber.In, this paper, Y-branched polymer optical waveguide couplers with SI and GI square cores are fabricated using the imprint method in order to apply to a multiplexing (MUX) device in the MMF WDM links. To fabricate low loss MUX devices, three different Y-branch structures are designed and actually fabricated. Then, their optical characteristics are compared. It is confirmed that the loss of GI waveguide is lower than that of SI waveguide, independent of the multiplexing structure, because the light leakage at the multiplexing region (two-cores junction) could be reduced due to the strong light confinement effect.